COMPARISON OF PHYSICAL ACTIVITY LEVEL BETWEEN COLOMBIAN AND BRAZILIAN PHYSICAL EDUCATION STUDENTS - Castaño, Luz Albany Arcila; Uchida, Marco Carlos; Barbieri, João Francisco; Sampaio, Ricardo Aurélio Carvalho; Sampaio, Priscila Yukari Sewo; Correia, Renan Felipe; Cardona, Hernan Mauricio Garcia; Garcia, Carlos Eduardo Nieto (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Evidence suggests that populations of developing countries present high levels of sedentarism. In contrast, it is also shown that educational level and access to information regarding the health benefits of exercise can raise a population’s level of physical activity (LPA). Thus, the present study aimed to evaluate the morphological profile (MP), level of physical activity (LPA) and cardiovascular risk among Brazilian (BPES) and Colombian physical education students (CPES) in an effort to determine if these specific subjects presented different results among themselves and in relation to normative data for each country. Method: The subjects, 59 BPES and 65 CPES, were evaluated through IPAQ in its short form, and had their MP determined through a bioelectric scale and waist measurement to determine the cardiovascular risk. Results: As result we verified that between BPES and CPES only waist circumference (WC) had significant difference (p = 0.016), being higher for CPES males. Comparing the results of the subjects with normative data, with the exception of CPES males, we observed higher LPA, better MP, and lower WC values. Female CPES were more active than their male peers, the opposite being true for the Brazilian subjects. Conclusion: We conclude that the repetitive exposition to information regarding the benefits of physical activity and the access to installations that allows for its practice not only raises LPA of physical education students, but also improves, in general, their MP and cardiovascular risk.